Tunnelling in low-temperature hydrogen-atom and proton transfers - Arnaut, Luís G. (2006)
The reaction path of the interacting-state model with the Lippincott-Schroeder potential for hydrogen bonds, is used in transition-state theory calculations with the semiclassical correction for tunnelling (LS-ISM/scTST) to estimate proton and hydrogen-atom transfer rates at low temperatures. Down to 100 K, the semiclassical correction leads to semi-empirical rates and isotope effects that are in good agreement with the thermal tautomerism of porphine, and the excited-state tautomerisms of salicylideneanilines and 2-(2'-hydroxyphenyl)benzoxazole. For lower temperatures, the tunnelling corrections become extremely high and unreliable. It is shown that the permeability of an Eckart barrier fitted to the curvature of the LS-ISM reaction path leads to good estimates of these reaction rates down to 2 K.